O funcionamento de nomes próprios no processo de referenciação - Bassetto, Lívia Maria Turra [UNESP] (2015)
The present work has as theoretical base the conception of referent presented by Textual Linguistics of socio-cognitive-interactionist base line. From this point of view, the referenciation is no longer seen as a relation of mirroring between language and reality, but as a process of referential construction that occurs in the discourse and, therefore, without a specular relation with the object of world. Hence, the referent has been considered object of discourse, since its construction occurs discursively whereof the verbal interaction, i.e., it is socio-culturally constructed starting from the social practices and remolded, in the interior of the discourse, in the function of the verbal interlocutors' comunicative purposes. Based on this theoretical support, this qualitative/interpretative research aimed to investigate the functioning of proper names, used in different contexts of verbal interaction, as strategies of referential construction, since there were no studies about it and only the designative function of the proper name was, without, therefore, (re)categorizing the referent. Differently from what the theory of Referenciation foresaw, this investigation aimed to demonstrate as, in particular situations of use, the proper name can be: (a) designative, in its more prototypic use; (b) attributive, being the characteristics constructed socio-cognitively in the verbal interaction; and (c) attributive, with more crystallized characteristics, being nearer the common name. Thus, these three modes of functioning of proper names constitute points of a continuum that starts from the designative proper name to the eponym - common name -, being the points (b) and (c) among them. To demonstrate these cases, texts of different genres (chronicles, newspaper reports, news, among others) were linguistically analyzed, emphasizing the use of proper names in different situations in the ...